a(n) = a(1) + d(n - 1)
a(7) + a(29) = a(1) + 6d + a(1) + 28d = 2a(1) + 34d = 2(a(1) + 17d) = 2a(18)
2a(18) = 59.2
a(18) = 29.6 ответ Е
ответ: E) 29,6.
Объяснение:
Найдите а18 в арифметической прогрессии (аn), если a7+a29=59,2.
Решение.
an=a1+(n-1)d.
a18=a1+17d.
a7=a1+6d;
a29=a1+28d;
a1+6d+a1+28d=59.2;
2a1+34d=59.2; [:2]
a1+17d=29.6;
Но a1+17d=а18. Значит
а18=29,6.
a(n) = a(1) + d(n - 1)
a(7) + a(29) = a(1) + 6d + a(1) + 28d = 2a(1) + 34d = 2(a(1) + 17d) = 2a(18)
2a(18) = 59.2
a(18) = 29.6 ответ Е
ответ: E) 29,6.
Объяснение:
Найдите а18 в арифметической прогрессии (аn), если a7+a29=59,2.
Решение.
an=a1+(n-1)d.
a18=a1+17d.
a7=a1+6d;
a29=a1+28d;
a1+6d+a1+28d=59.2;
2a1+34d=59.2; [:2]
a1+17d=29.6;
Но a1+17d=а18. Значит
а18=29,6.